Clinical study status of diabetic gastrointestinal diseases - Fan, Xuechun; Wang, Yanyan; Cao, Jingsi; Yu, Jing; Tian, Jiaxing; Mi, Jia (Frontiers in Endocrinology, 2025)
BackgroundDiabetic gastrointestinal diseases not only affect the quality of life of patients, but also bring heavy economic burden to patients. Understanding of the current features of diabetic gastrointestinal diseases-related clinical trials are important for improving designs of clinical trials and identifying neglected areas of study. Despite the high prevalence of gastrointestinal complications among diabetic patients, comprehensive analyses of registered clinical trials are lacking. This study aimed to present a scoping overview of diabetic gastrointestinal diseases-related clinical trials registered in ClinicalTrials.gov, ChiCTR and high-quality diabetic gastrointestinal diseases-related clinical trials published in Pubmed in the past 10 years.MethodsThe trials registered in ClinicalTrials.gov and ChiCTR databases from the establishment of the database to June 14,2024 were searched. Moreover, high-quality trials with impact factors of 5 points or more published in Pubmed from June 2014 to June 2024 were searched. The results were extracted and presented in tabular form.ResultsMost studies focused on diabetic gastroparesis, with drug interventions being the most common. In addition, most studies were small sample sizes (≤100), randomized parallel controlled trials and 69.01% of the studies used different methods of blinding. Most studies did not conduct safety evaluation and follow-up.ConclusionThe diagnostic criteria of diabetic gastrointestinal diseases were diverse. Furthermore, most studies on diabetic gastrointestinal diseases focused on diabetic gastroparesis. There was considerable heterogeneity in study designs and efficacy evaluations.